PENGARUH MOTIVASI, PERSEPSI, DAN SIKAP TERHADAP KEPUTUSAN MAHASISWA MEMILIHUNIVERSITAS BUNG HATTA PADANG - Zeshasina Rosha (Jurnal Apresiasi Ekonomi, 2017)
This study aimed to identify and analyze the influence of motivation, perceptions, and attitude of students toward the decision of choosing the Bung Hatta University. The approach in this study was a case study with quantitative descriptive method. These samples included 318 people who were taken with random sampling technique cluster proportionate. Data analyzed was performed by using partial test (t-test) to determine the effect of each independent variable on the dependent variable. The result showed that: (1) motivation significantly influenced the student's decision in selecting Bung Hatta University in Padang; (2) perception significantly influenced the student's decision in selecting Bung Hatta University in Padang; (3) the attitude did not affect the decision of the students chose the Bung Hatta University in Padang. Keywords: motivation, perception, attitude, and the election decision